2016
DOI: 10.1186/s40902-016-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morbidity, mortality, and risk factors of tracheostomy-related complications in patients with oral and maxillofacial cancer

Abstract: BackgroundThis study aimed to analyze and describe the morbidity and mortality associated with tracheostomy in patients with oral cancer and to identify the risk factors associated with tracheostomy complications.MethodsWe performed a retrospective chart review of patients who underwent tracheostomy during a major oral cancer resection between March 2001 and January 2016 at the National Cancer Center, Korea. Overall, we included 51 patients who underwent tracheostomy after oral cancer surgery. We assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…3,5 It appears that the popularity of immediate mandibular surgical intervention has increased with improved technologies such as mandibular distraction osteogenesis, and this likely relates to tracheostomy-related complications, which pose significant risk of morbidity and mortality. 4 Previous studies have demonstrated significant relief of upper airway obstruction following mandibular distraction osteogenesis for patients with mandibular hypoplasia at early intervention (2.5 months) 5 and at long-term follow up, but these cases require the presence of at least a portion of the ramus-condyle subunit, not present in our patient. 6 Bone allografts, particularly in the well-vascularized infant craniofacial skeleton, may offer particular promise for craniofacial reconstruction.…”
Section: Discussionmentioning
confidence: 62%
“…3,5 It appears that the popularity of immediate mandibular surgical intervention has increased with improved technologies such as mandibular distraction osteogenesis, and this likely relates to tracheostomy-related complications, which pose significant risk of morbidity and mortality. 4 Previous studies have demonstrated significant relief of upper airway obstruction following mandibular distraction osteogenesis for patients with mandibular hypoplasia at early intervention (2.5 months) 5 and at long-term follow up, but these cases require the presence of at least a portion of the ramus-condyle subunit, not present in our patient. 6 Bone allografts, particularly in the well-vascularized infant craniofacial skeleton, may offer particular promise for craniofacial reconstruction.…”
Section: Discussionmentioning
confidence: 62%
“…We report a total complication rate of 22%, which is less than some previous studies report, despite we recorded also medical complications. Lee et al [ 5 ] reported tracheostomy complication rate of 43% in patients with major oral cavity cancer resection. However, they did not report medical complications.…”
Section: Discussionmentioning
confidence: 99%
“…The tracheotomy group exhibited a significantly higher prevalence of several variables compared to the non-tracheotomy group (all p values <0.0001). These factors included: (1) tumors located at the gum, mouth floor, retromolar subsites, (2) male sex, (3) pT3-4 disease, (4) pN2-3 disease, (5) p-Stage IV, (6) poorly differentiated tumor, (7) clear margins (≥5 mm), (8) deeper DOI, (9) reconstruction with free flap reconstruction, (10) treatment involving surgery and adjuvant therapy, (11) higher weighted Charlson comorbidity index (CCI), 19 and ( 12) prolonged hospital stays.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This strategy has led to tracheotomy rates that fluctuate between 14% 12 and 34%. 13 Although elective tracheotomy is associated with certain complications [7][8][9]11 and has been reported to influence survival rates, 10 some researchers have observed that surgeries for OCSCC, which often necessitate tracheotomy, do not typically lead to severe complications or significantly affect the overall outcomes. 9,11 Anecdotal evidence from our clinical practice suggests that tracheostomy may not have a substantial influence on the survival outcomes of patients with OCSCC.…”
Section: Introductionmentioning
confidence: 99%